Pengaruh Economic Value-Added dan Market Value Added terhadap Harga Saham pada Perusahaan Sektor Healthcare - Michelle, Michelle; Nainggolan, Olivia Venessa (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
According to the Central Statistics Agency (BPS) (2020), the economic sector experienced a sharp decline in income during the Covid-19 pandemic, which ranged from 70.67% to 87.93%. However, it is inversely proportional to the pharmaceutical sector companies which have experienced an increase in sales of goods and services, this is due to the fact that during the pandemic medical devices became the main needs of the general public. Seeing this phenomenon, the authors conducted a study that aimed to find out the effect of EVA and MVA on stock prices in Healthcare sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The author uses purposive sampling method in this study. The results of this study show that partially, Economic Value Added does not have a significant effect on stock prices, while Market Value Added has a significant influence on stock prices. Simultaneously, Economic Value Added and Market Value Added affect the share price of Healthcare companies on the Indonesia Stock Exchange for the 2019-2022 period.